Magnetic properties of sintered CoFe2O4-BaTiO3 particulate magnetoelectric composites - Mohan, S.; Joy, P. A. (Ceramics International, 2019)
The magnetic properties of sintered particulate magnetoelectric CoFe2O4 - BaTiO3 composites have been studied. The particulate composites are sintered in the temperature range 1000-1300 degrees C, for a short duration of 10 min. The magnetic transition temperature (T-c) of CoFe2O4 is found to decrease with increasing the sintering temperature and sintering time, as well as on increasing the BaTiO3 content in the composites. Similarly, a reduced saturation magnetization at room temperature, compared to that expected for the CoFe2O4 content, is also observed. Powder X-ray diffraction studies showed the presence of the impurity phase related to the hexagonal ferrite BaFe12O19 in all the composites. Ba2Fe2Ti4O13 is observed as a second impurity phase in the BaTiO3 - rich composites. The present studies suggest that the composition of the piezomagnetic (CoFe2O4) phase in the CoFe2O4 - BaTiO3 magnetoelectric composite is affected during the sintering process.
Keywords: composites; magnetic properties; Sintering

Renewable synthesis of MoO3 nanosheets via low temperature phase transition for supercapacitor application - Sankar, K. N. Amba; Kesavan, Lokesh; Saha, Bikash; Jyolsnaraj, M. K.; Mohan, S.; Nandakumar, P.; Mohanta, Kallol; Kvarnstroem, Carita (SCIENTIFIC REPORTS, 2024)
Keywords: alpha-MoO3; h-MoO3; Mixed phases (h and alpha) of MoO3; Renewable green synthesis; Very low temperature phase transition

Binder-free in situ interface reconstruction of NiMoO4 nanorods over Ni(OH)2 nanosheets for efficient urea oxidation - Kumar, Yogesh; Barik, Sidharth; Kharabe, Geeta Pandurang; Torris, Arun; Singh, Mayank U.; Mohan, S.; Galave, Chaitanya; Tekawadia, Jyoti; Kanawade, Rajesh; Kurungot, Sreekumar (Advanced Sustainable Systems, 2025)
Replacing the energy-intensive oxygen evolution reaction (OER) with the urea oxidation reaction (UOR) in electrochemical water splitting offers simultaneous green hydrogen production and urea-rich wastewater oxidation, enhancing energy efficiency and economic viability. In this study, a non-noble metal-based binder-free NiMoO4/Ni(OH)2/NF electrocatalyst is developed, featuring NiMoO4 nanorods anchored on Ni(OH)2 nanosheets. This unique morphology facilitates a highly active in situ reconstructed interface, delivering a current density of 134 mA cm-2 at 1.40 V (vs RHE) in 1 m KOH with 0.33 m urea, significantly outperforming its individual components. The catalyst demonstrates excellent stability over 50 h at 30 mA cm-2. When integrated into an anion exchange membrane urea electrolyser (13 cm2 area) with Pt@C/NF as the HER cathode, the system achieves 192 mA cm-2 at 1.60 V. The post-UOR studies confirm the presence of an amorphous NiMoO4-crystalline Ni(OH)2 interface, which plays a key role in enhancing the availability of the active sites to enhance the UOR performance. The improved electrochemical performance of the engineered catalyst can be ascribed to the in situ reconstructed amorphous-crystalline interface, optimal hydrophilicity, reduced charge transfer resistance, and the distinct morphology. This strategy offers a promising pathway for developing highly active electrocatalysts for energy conversion applications.
Keywords: AEM; electrolyser; OWS; tomography; UOR; wastewater

Unlocking efficient water splitting through Fe-induced activity enhancement in NiCo2O4 bifunctional electrocatalysts - Sankar, K. N. Amba; Mahana, Debashrita; Mohan, S.; Gupta, Suryakant B.; Hussain, Amreen A. (Journal of Materials Science, 2026)
The development of efficient, durable and inexpensive bifunctional electrocatalysts is essential for advancing overall water splitting technologies. In this study, we present a novel strategy involving dilute Fe doping in NiCo2O4 (NCO) spinel structures to enhance their electrocatalytic activity and stability. Fe was introduced at varying concentrations, and the resulting Fe-doped NCO catalysts were systematically characterized to understand their structural, morphological, and surface properties. Comprehensive structural and surface analyses revealed the successful incorporation of Fe ions into the NCO lattice without altering its intrinsic spinel framework. Brunauer-Emmett-Teller (BET) analysis showed that the NCO-Fe1 sample exhibited the highest surface area (41.82 m2g-1) and the smallest pore size, facilitating enhanced ion diffusion and exposure of active sites. Electrochemical studies revealed a pronounced improvement in bifunctional catalytic activity for the NCO-Fe1 catalyst, which delivered low overpotentials of 228 mV for the hydrogen evolution reaction (HER) and 274 mV for the oxygen evolution reaction (OER) at 10 mAcm-2. The corresponding Tafel slopes of 151 mVdec-1 (HER) and 52.54 mVdec-1 (OER) indicate favourable reaction kinetics and efficient charge-transfer dynamics. Furthermore, the overall water-splitting device constructed using NCO-Fe1 electrodes required only 1.72 V at 10 mAcm-2 to sustain continuous operation, maintaining excellent durability over 300 h of testing without significant performance degradation. Hence, this study provides new insights into the role of dilute dopant engineering in multicomponent oxides and establishes NCO-Fe1 as a promising, high-performance, and durable bifunctional electrocatalyst for sustainable water-splitting applications.